Solid‐Waste‐Derived Carbon Dioxide‐Capturing Materials. Issue 10 (2nd April 2019) - Wang, Junya; Yang, Ying; Jia, Qingming; Shi, Yuzhen; Guan, Qingqing; Yang, Na; Ning, Ping; Wang, Qiang
Abstract: Solid sorbents are considered to be promising materials for carbon dioxide capture. In recent years, many studies have focused on the use of solid waste as carbon dioxide sorbents. The use of waste resources as carbon dioxide sorbents not only leads to the development of relatively low‐cost materials, but also eliminates waste simultaneously. Different types of waste materials from biomass, industrial waste, household waste, and so forth were used as carbon dioxide sorbents with sufficient carbon dioxide capture capacities. Herein, progress on the development of carbon dioxide sorbents produced from waste materials is reviewed and covers key factors, such as the type of waste, preparation method, further modification method, carbon dioxide sorption performance, and kinetics studies. In addition, a new research direction for further study is proposed. It is hoped that this critical review will not merely sum up the major research directions in this field, but also provide significant suggestions for future work. Abstract : So‐solid CO2 : The use of waste resources as carbon dioxide sorbents not only leads to the development of relatively low‐cost materials, but also eliminates waste simultaneously. Herein, progress on the development of these carbon dioxide sorbents is reviewed with a focus on the type of waste, preparation method, further modification method, carbon dioxide sorption performance, and kinetics studies.